Penerapan Metode CIRC (Cooperative Integrated Reading and Composition) dalam Pembelajaran Pendidikan Agama Islam di SDN 20 Kota Bengkulu - Fina Sofiana; Suhirman Suhirman; Khairiah Khairiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the implementation of the Cooperative Integrated Reading and Composition (CIRC) method in Islamic Education learning at SDN 20 in Bengkulu City. The research method used is descriptive qualitative with research subjects consisting of 28 sixth-grade students and teachers teaching Islamic Education at SDN 20 in Bengkulu City. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of the CIRC learning method involves all school authorities, supportive facilities and infrastructure, media selection, modes, strategies, and lesson plan preparation by Islamic Education teachers. With the implementation of this learning model, students are able to understand reading texts and solve issues within the readings. The CIRC learning method is considered effective as it enhances student engagement, makes them enjoy the learning process, and aids in understanding readings without feeling bored. Based on the research findings, it is concluded that the application of the CIRC method is effective in Islamic Education learning at SDN 20 in Bengkulu City. This method enhances students' understanding of Islamic concepts and their ability to apply religious values in daily life. Therefore, it is recommended to continue implementing the CIRC method in Islamic Education teaching to enhance the quality of learning and students' learning outcomes consistently. Keywords: CIRC Method, Islamic Education, Implementation